2022
DOI: 10.2147/ccid.s378798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the in vitro Anti-Inflammatory Effect of Cannabidiol to Dexamethasone

Abstract: Background Cannabidiol (CBD) is a non-psychoactive phytocannabinoid constituent of Cannabis sativa with pain-relieving and anti-inflammatory properties. With the emphasis on natural ingredients in cosmetics, CBD has become a new cosmetic ingredient due to its ability to alleviate inflammation. However, in-depth studies that directly compare the effective mechanism and the therapeutic potential of CBD are still needed. Purpose The aim of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…When macrophages are exposed to LPS, inflammatory mediators such as IL-6 are released [ 52 ]. Recently, it was reported that treatment with CBD (0.02 mg/mL) significantly inhibited the LPS-induced levels of IL-6 and TNF-α produced in RAW264.7 cell macrophages [ 53 ]. In this study, the ability of CBD extract and CBD-NLCs to inhibit or reduce the production of IL-6 was studied in RAW264.7 cell macrophages by evaluating the concentrations of IL-6 in the culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…When macrophages are exposed to LPS, inflammatory mediators such as IL-6 are released [ 52 ]. Recently, it was reported that treatment with CBD (0.02 mg/mL) significantly inhibited the LPS-induced levels of IL-6 and TNF-α produced in RAW264.7 cell macrophages [ 53 ]. In this study, the ability of CBD extract and CBD-NLCs to inhibit or reduce the production of IL-6 was studied in RAW264.7 cell macrophages by evaluating the concentrations of IL-6 in the culture supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…The suppressive in vitro inhibitory effects of CBD on the production and release of IL1, IL8, and CXCL1 have also been previously shown in other pre-clinical in vitro inflammatory models using various cell types, including monocytes [70], macrophages [71], epithelial cells, and fibroblasts [72,73], stimulated with LPS or TNFα. A previous study showed that CBD has a similar anti-inflammatory effect to dexamethasone in macrophages by attenuating the LPS-induced production of NO, IL6, and TNFα through inhibition of NFκB p65 phosphorylation [74]. Since the molecular mechanism underlying the observed anti-inflammatory effects of CBD in urothelial cells has never been studied before, we next investigated the activation of the transcription factor NFκB, which plays a central role in chronic inflammatory diseases characterized mainly by an inflammatory and innate immune response, including IC/BPS [75][76][77][78].…”
Section: Discussionmentioning
confidence: 97%
“…Numerous publications have demonstrated the potent anti-inflammatory effect of CBD both in-vitro and in-vivo [ 13 , 57 , 58 ]. The underlying mechanisms involve direct suppression of the activation of different types of immune cells, induction of apoptosis, and promotion of regulatory cells, which in turn control other immune cell targets.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro and ex vivo studies have demonstrated that CBD possesses anti-inflammatory properties. Mechanistically, this is due to its modulation of the TLR4 signal transduction cascade and altered activation of the transcription factors NF-κB (nuclear factor κ-light-chain-enhancer of activated B cells) or AP-1 (activating protein-1), leading to lower levels of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%